CBIS-TV (Calamba Bayside Integrated School- TV): A Contextualized Supplemental Live Online Tutorial for Learners - Gecolea, Cincy Merly B.; Pagulayan , Elsa D.; Pantoja , Judy Mae S.; Diaz , Marian B. (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
This study was conducted to determine the relationship between the level of observation in the implementation of CBIS-TV and the level of its assessed effectiveness. The study used a descriptive-correlational research design. The respondents of the study were the 258 students of Calamba Bayside Integrated School. A simple random sampling technique was utilized to determine the respondents of the study. The results of the study revealed that all respondents have the same level of observation in the implementation of CBIS-TV, which is observed. It also disclosed that all respondents agreed that CBIS-TV is effective in assisting learners in answering learning tasks, supporting transfer of learning, and increasing students' motivation to study. Moreover, it also revealed that there is a significant relationship between the level of observation in the implementation of CBIS-TV and its level of effectiveness. It implies that CBIS-TV is proven to be highly effective as a contextualized supplementary online tutorial platform for learners. It also improves the quality of learning in the distance learning setup. It is recommended that this initiative be implemented for year two and the researchers may investigate its effectiveness in improving the academic performance of the learners.